2018
DOI: 10.1002/rcm.8024
|View full text |Cite
|
Sign up to set email alerts
|

Improving negative liquid chromatography/electrospray ionization mass spectrometry lipidomic analysis of human plasma using acetic acid as a mobile‐phase additive

Abstract: Acetic acid at a concentration of 0.02% (v/v) is the suggested choice as a mobile-phase additive for lipidomics and targeted lipid profiling with negative LC/ESI-MS based on signal enhancement and improved lipid coverage compared to ammonium acetate, ammonium acetate with acetic acid and ammonium hydroxide mobile phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 37 publications
1
13
1
1
Order By: Relevance
“…Fourth, among the utilized ammonium salts, the ESI (−) mass spectral responses of the GD1 ions were the highest with AmBc (Figure 3D versus 3B and C and Figure S6). The effects of the acid and neutral salt additives on the mass spectral responses with ESI (−) have been extensively investigated [40][41][42][43]. For example, the effects of AmF and AmAc additives on ESI (−) MS of selective androgen receptor modulators were compared and the results, which are also consistent with ours, indicated that the signal suppression effect of AmAc was smaller than that of AmF (Figure 3B versus 3C) [40].…”
Section: Evaluation Of Ammonium Salt Additives For Lc−ms Of Gd1 Isomerssupporting
confidence: 74%
See 1 more Smart Citation
“…Fourth, among the utilized ammonium salts, the ESI (−) mass spectral responses of the GD1 ions were the highest with AmBc (Figure 3D versus 3B and C and Figure S6). The effects of the acid and neutral salt additives on the mass spectral responses with ESI (−) have been extensively investigated [40][41][42][43]. For example, the effects of AmF and AmAc additives on ESI (−) MS of selective androgen receptor modulators were compared and the results, which are also consistent with ours, indicated that the signal suppression effect of AmAc was smaller than that of AmF (Figure 3B versus 3C) [40].…”
Section: Evaluation Of Ammonium Salt Additives For Lc−ms Of Gd1 Isomerssupporting
confidence: 74%
“…Therefore, it was clear that the anions of the salt additives affected the mass spectral responses in ESI (−). Further, the stronger basic character of the bicarbonate anion, compared to the acetate and formate anions, could explain the mild signal suppression of GD1 in ESI (−) with AmBc but this was not solely responsible since other factors such as anion volume and organic modifier also exerted significant effects on the ESI (−) response [40,43]. Similar separation and ionization behaviors were also observed using the 1.7-μm C18 column (Figure S7).…”
Section: Evaluation Of Ammonium Salt Additives For Lc−ms Of Gd1 Isomersmentioning
confidence: 66%
“…Konduktivitas digunakan untuk mengukur daya hantar larutan atau cairan elektrolit. Besarnya konduktivitas ditentukan oleh konsentrasi elektrolit (17,(146)(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159) . Energi listrik dapat di transfer melalui materi berupa hantaran yang bermuatan listrik yang berwujud arus listrik yang berarti bahwa harus ada pembawa muatan listrik di dalam materi serta adanya gaya yang menggerakkan pembawa muatan tersebut (57,(68)(69)(70)(71)(72)(73) .…”
Section: Gambar 6 Ikatan Kovalen Koordinasi Nh4 + (47)unclassified
“…The wide concentration range of metabolites presented in biological samples, the diversity of physical and chemical properties of the metabolites related to various classes (amino acids, lipids, and carbohydrates), and so forth, prevent the correct detection of numerous sample metabolites by one analytical approach [5,6,7]. The application of various additives to enhance the ESI ionization efficiency of a wide range of metabolites is one of the routine laboratory methods for improving coverage [7,8]. The inclusion of additives in the spray solvent is a simple, fast, and easily reproducible method that enables bypassing the problem of nondetectability of some analytes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there is no consensus on the selection of the optimal additives for negative ESI mode (ESI(−)) [8]. The lack of full understanding of the ESI(−) process is a reason for this paradox.…”
Section: Introductionmentioning
confidence: 99%